Influence of ‘Bergendang’ Culture in the Spaces of Traditional Sarawak Malay House - Yon Syafni, Samat; Syed Iskandar, Ariffin; Nurakmal, Abdullah Goh; John Ting, Hwa Seng (e-International Publishing House, Ltd., 2023)
Bergendang is a uniquely Sarawak Malay traditional entertainment frequently held during social gatherings at home. This paper investigates the spatial use of bergendang activity in traditional Malay houses along the Sarawak River in Kuching. The research employed a qualitative case study design approach through field study observation and semi-structured interviews. Findings revealed different spatial use of bergendang for the early and later models of Sarawak Malay houses, which is associated with house owners’ social status. Spatial studies on traditional Malay houses in other parts of Sarawak are recommended for constructing northern Borneo's vernacular Malay house framework.